2014
DOI: 10.1128/ec.00273-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Apt1 Protein in Polysaccharide Secretion by Cryptococcus neoformans

Abstract: e Flippases are key regulators of membrane asymmetry and secretory mechanisms. Vesicular polysaccharide secretion is essential for the pathogenic mechanisms of Cryptococcus neoformans. On the basis of the observations that flippases are required for polysaccharide secretion in plants and the putative Apt1 flippase is required for cryptococcal virulence, we analyzed the role of this enzyme in polysaccharide release by C. neoformans, using a previously characterized apt1⌬ mutant. Mutant and wild-type (WT) cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 72 publications
8
76
1
Order By: Relevance
“…Our previous studies also demonstrated that aptl Δ cells had defective GXM secretion during in vitro regular growth, in the presence of host cells and in vivo, which is in agreement with the observation of aberrant Golgi morphology [26]. Since GXM synthesis is Golgi-associated [19], we asked whether APT1 deletion would impact intracellular GXM detection.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Our previous studies also demonstrated that aptl Δ cells had defective GXM secretion during in vitro regular growth, in the presence of host cells and in vivo, which is in agreement with the observation of aberrant Golgi morphology [26]. Since GXM synthesis is Golgi-associated [19], we asked whether APT1 deletion would impact intracellular GXM detection.…”
Section: Resultssupporting
confidence: 82%
“…Previous studies demonstrated that deletion of APT1 in C. neoformans did not affect PS exposition and lipid translocation across the plasma membrane [26]. Instead, aptlΔ cells showed an abnormal distribution of Golgi membranes and a defect in membrane trafficking during endocytosis [26,37], suggesting intracellular localization of the protein encoded by APT1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations